REFORMULASI KETENTUAN PASAL40 AYAT 2 UNDANG-UNDANG NOMOR 5 TAHUN 1990TENTANG KONSERVASI SUMBER DAYA ALAM HAYATIDAN EKOSISTEMNYA TERHADAP PELAKU EKSPLOITASI HEWAN DALAM PERSPEKTIFHUKUM PIDANA INDONESIA - Rizki Pratama Kaloko; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Exploitation of animals in recent times often occur in the territory of Indonesia both from the use to the destruction of these animals. In this case it is explained in Article 33 Paragraph (3) of the 1945 Constitution, which explains that "the earth and water and the natural resources contained therein are controlled by the state and used for the greatest prosperity of the people." But one problem that arises is that if we look at current reality, that the application of sanctions or penalties against the perpetrators of animal exploitation is not running properly, so it does not provide a deterrent effect on the perpetrators. The use of legal remedies, including criminal law as an effort to overcome social problems, including in the field of law enforcement policies.The type of research / approach used by the author is normative legal research, namely library law, because it makes library material as the main focus. In this normative legal research the writer conducts a study of legal systematics carried out by examining the basic understanding of the legal system contained in legislation. Where the author is guided by the provisions in force.From this research, it can be concluded that in terms of implementation related to reformulation in animal exploitation, we need to understand or know about Law Number 5 of 1990 regulating the Conservation of Living Natural Resources and Ecosystems, the utilization of which is carried out wisely to ensure the continuity of its supplies while maintaining and increasing the quality of diversity and its value. Besides that, in terms of the idea of the provisions of Article 40 Paragraph 2 of Law Number 5 of 1990 regulating the Conservation of Biological Resources and their Ecosystems against animal exploiters the need for renewal in the perspective of criminal law certainly cannot be released with the values of life and culture of a nation.Keywords: Reformulation, Animal-Exploiters